An organic semiconductor/metal Schottky heterojunction based direct current triboelectric nanogenerator windmill for wind energy harvesting. (May 2023) - You, Zhong yuan; Wang, Xin; Lu, Fuqi; Wang, Shuting; Hu, Bingxi; Li, Lian; Fang, Weihai; Liu, Ying
Abstract: In this work, we design and fabricate a miniature direct current (DC) windmill generator based on dynamic semiconductor/metal Schottky triboelectric nanogenerators (TENGs), demonstrating a novel way for DC electrical power generation by harvesting wind energy. The semiconducting Poly(3, 4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) film and metallic Al foil are designed as the positive-negative friction pair in the DC-TENG, and the softness as well as workability of the friction materials provides excellent flexibility for the design and tailor of a windmill DC-TENG. We systematically studied the effect factors on the output performance of the device, including wind speed, external load, and dimensions of the friction layers. Our device achieves an optimal output performance with a maximum open-circuit voltage (Voc ) of 0.6 V and a maximum short-circuit current (Isc ) of 3.6 μA at the wind speed of 7 m/s for the friction layer area at 2.5 cm 2 . To improve the wear resistance of the devices, we introduce a few lubricating materials at the PEDOT:PSS /Al interface and Polyalphaolefin 4 (PAO 4) can improve both the abrasiveness as well as the Voc and Isc . Our work presents a possible strategy for fabricating miniature windmill DC-TENG and provides a potential supplemental for the traditional electrical magnet windmill with heavy equipment. Graphical Abstract: In this work, we design and fabricate a miniature direct current (DC) windmill generator based on dynamic semiconductor/metal Schottky triboelectric nanogenerators (TENGs), demonstrating a novel way for DC electrical power generation by harvesting wind energy. The semiconducting Poly(3, 4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) film and metallic Al foil are designed as the positive-negative friction pair in the DC-TENG, and the softness as well as workability of the friction materials provides excellent flexibility for the design and tailor of a windmill DC-TENG. We systematically studied the effect factors on the output performance of the device, including wind speed, external load, and dimensions of the friction layers. Our device achieves an optimal output performance with a maximum open-circuit voltage (Voc ) of 0.6 V and a maximum short-circuit current (Isc ) of 3.6 μA at the wind speed of 7 m/s for the friction layer area at 2.5 cm2. To improve the wear resistance of the devices, we introduce a few lubricating materials at the PEDOT:PSS /Al interface and Polyalphaolefin 4 (PAO 4) can improve both the abrasiveness as well as the Voc and Isc. Our work presents a possible strategy for fabricating miniature windmill DC-TENG and provides a potential supplemental for the traditional electrical magnet windmill with heavy equipment. ga1 Highlights: A wind energy harvesting TENG based on tribovoltaic effect was prepared and the capacitor charging was realized. The influence of wind speed, load and friction layer area on the output performance of the device was investigated. The Voc and Isc and its working life of the device are improved by interface lubrication.